the questions without numbers kill me
here's my work, I have no answer to know if I'm right
bx = c-x
bx = c-x
x x
x= b +1/ c
if anyone can help, I'd appreciate it
Thanx
The inter net does not respect spaces. You mean (bx)/x= (c- x)/x
That is b= (c/x)- 1
c/x= b+ 1
Two errors- strictly speaking this means x= b+ (1/c) and what I think you meant was x= (b+ 1)/c- which is still wrong. if you divide both sides of c/x= b+ 1 by c you still have the x in the denomator on the left. you should have 1/x= (b+1)/c.x= b +1/ c
Now, you can invert both sides to get x= c/(b+ 1).
If anyone can help, I'd appreciate it.
Thanx